Online Course Design: A Review of the Canvas Course Evaluation Checklist - Baldwin, Sally J.; Ching, Yu-Hui (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
The evaluation of online courses is an important step in providing quality online courses. There are a variety of national and statewide evaluation tools used to help guide instructors and course designers of online courses (e.g., Quality Matters, OSCQR). This paper discusses a newly released course evaluation instrument from Canvas, the second largest learning management system (LMS) used by higher education institutions in the United States. The characteristics and unique features of the Canvas Course Evaluation Checklist (CCEC) are discussed. The CCEC is also compared to established national and statewide evaluation instruments. This review is helpful for those interested in online course design and developments in the field of online education.